Grid compliance for the land based electrical power generators - Yang, Shicong (Nanyang Technological University, 2019)
The fault ride-through (FRT) or low voltage ride-through (LVRT) is one of the critical requirements in the grid codes or distribution codes. The codes are normally defined by the grid operators or the local authority, and generators connecting to a grid are required to comply with all the relevant requirements stated in the code. The LVRT requirement was initially established and applied to wind power generators connecting to power grids. But it is now applied to all generators in many recent revised codes regardless of the technologies used. Complying with the LVRT requirement is very challenging for distributed synchronous generators due to the rotor angle stability during fault transients. Many ways and means for LVRT capability enhancement have been researched for wind generators, but only limited researches have been conducted for LVRT capability enhancement for distributed synchronous generators. This work is focused on developing topologies and control strategies for LVRT capability enhancements for engine synchronous generators, an example of distribution synchronous generators (DSG).